Differences in the educational paths of entrepreneurs and employees - Backes-Gellner, Uschi [Verfasser]; Tuor Sartore, Simone N. [Verfasser]; Wettstein, Daniela [Verfasser] (My University, 2010)
"This paper examines whether individuals who become either entrepreneurs or employees follow systematically different educational paths to a given educational level. Following Lazear's jack-of-all-trades theory, we expect that entrepreneurs aim at a balanced set of different skills - that is, they combine academic and vocational skills - while employees specialize in one skill. This means that entrepreneurs follow educational paths that combine different types of education, while employees follow same-type paths while climbing up the educational ladder. We use the Swiss Labor Force Survey to test our hypothesis. Our empirical findings are in line with Lazear's theory and indicate that individuals who change between different types of education and acquire a more balanced set of skills are more likely to become entrepreneurs. Thus, the permeability of a country-specific educational system is one crucial determinant of entrepreneurship." (Autorenreferat, BIBB-Doku)
Vorab veröffentlicht als "Leading House Working Paper No. 50": http://www.isu.uzh.ch/leadinghouse/WorkingPapers/0050_lhwpaper.pdf [Zugriff 27.12.2010]
Keywords: G 1.3.2 Bildungsverhalten und -verläufe; S 4.3.5 Bildungsbeteiligung & soziale Gerechtigkeit; I 2.2.1 Westeuropa; Bildungsverlauf; Bildungsniveau; Unternehmer; Angestellter; Durchlässigkeit im Bildungssystem; Schweiz